Victim Experiences and Perspectives on Police Responses to Verbal Violence in Domestic Settings. (October 2013) - Stewart, Catherine Carolyn; Langan, Debra; Hannem, Stacey
This interdisciplinary, qualitative study explores why individuals called the police in noncriminal, verbally aggressive situations and how they perceived police responses. In-depth interviews were conducted with 30 individuals, mostly women. While some reported positive perceptions of the police response, the participants' accounts underscored the seriousness of verbal violence and revealed that when women seek help from police they often perceive the resulting response as inadequate and/or unfair. This study highlights the importance of recognizing that verbal violence is often part of a "fabric of abuse" that may include criminal behavior and considers implications for police practice.